SugarCRM developer's manual : customize and extend SugarCRM : learn the application and database architecture of this open-source CRM and develop and integrate your own modules and custom workflows /: customize and extend SugarCRM : learn the application and database architecture of this open-source CRM and develop and integrate your own modules and custom workflows. (2007) - Unknown
No abstract available